Vypočítejte derivace funkcí y = f (x) daných implicitně:
\( x^2 + 2xy − y^2 = 2x, y < x \) Vypočítejte \( f'(2) \).
\( y^2 = 2px , y > 0 \) derivative y^2 = 2px , y > 0
\( \sqrt{x} + \sqrt{y} = \sqrt{a} , y > 0 \) derivative sqrt(x) + sqrt(y) = sqrt(a)
\( \frac{x^2}{a^2} + \frac{y^2}{b^2} = 1, y>0 \) derivative x^2/a^2 + y^2/b^2 = 1, y>0
\( x^{2/3} + y^{2/3} = a^{\frac{2}{3}} , y > 0 \) derivative x^(2/3) + y^(2/3) = a^(2/3)
\( \arctan \frac{y}{x} = \ln \sqrt{x^2 + y^2}, y<x \) aan y/x = ln sqrt(x^2 + y^2), y<x